Speaking & pronunciation : course book - McCormack, Joan; Watkins, Sebastian; Smith, Jonathan; Margolis, Annette (Reading, UK : Garnet Education, 2010)
A university preparation course published in collaboration with the University of Reading.
Suitable for: TOEFL 500-600, IELTS 5.0-7.0. Includes 3 CDs: Speaking audio CD, Pronunciation audio CD1, and Pronunciation audio CD2
Keywords: English language -- Textbooks for foreign speakers; English language -- Pronunciation; Rhetoric -- Problems, exercises, etc; English language -- Rhetoric -- Problems, exercises, etc